Oral health-related quality of life, probable depression and probable anxiety: evidence from a representative survey in Germany - André Hajek; Hans-Helmut König (BMC, 2022)
Abstract Background There is limited knowledge regarding the association between oral health-related quality of life and probable depression and anxiety. Our objective was to examine the association between oral health-related quality of life and probable depression and anxiety in the German population (stratified by sex). Methods In sum, n = 3,075 individuals took part in a nationally representative survey (August/September 2021). The well-established Patient Health Questionnaire-9 (PHQ-9; cut-off of 10) and the Generalized Anxiety Disorder-7 (GAD-7; cut-off of 10) were used to quantify probable depression and anxiety, respectively. Results The likelihood of probable depression was significantly associated with lower oral health-related quality of life in the total sample (OR: 1.21, 95% CI: 1.18-1.25) and in both women and men. Additionally, the likelihood of probable anxiety was significantly associated with lower oral health-related quality of life in the total sample (OR: 1.17, 95% CI: 1.14-1.21) and in both women and men. Conclusions Our study emphasized the association between lower oral health-related quality of life and probable depression as well as anxiety in the general adult population in Germany. Future longitudinal studies are required to confirm our findings.